Use of DNA barcode in the identification of fish eggs in tributaries of the Paranapanema River basin - de Lima, Moema Cristina Costa (Genet Mol Biol, 2020)
Fish eggs are often excluded from identification analysis since at this stage of development there are few morphological characters. The correct identification of eggs can provide important information about spawning areas of species. The current work aimed to identify fish eggs in the Tibagi and Cinzas Rivers using the DNA barcode to obtain information on richness and diversity, adding to the existing data in the area. Of the 928 sequences analyzed using the BOLD Systems database, 99.78% were able to be identified at a specific level, demonstrating a high success rate for egg identification. The samples resulted in 25 species, 11 families, and 2 orders. Of the 25 species found, more than half (60%) present reproductive migration behavior, indicating that the tributaries of the Capivara reservoir are being used as a migratory route by these species. Eggs of rare and endangered species were found, indicating these tributaries as spawning grounds for these species. The results demonstrate the importance of identifying fish eggs in reservoir-influenced environments to recognize breeding areas of native and endangered species, as well as the importance of the Tibagi and Cinzas Rivers for the maintenance of native fish species in the Paranapanema River.